The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.20903/csnmbs.masa.2013.34.1-2.38
|View full text |Cite
|
Sign up to set email alerts
|

HYSTERESIS-LIKE FLATBAND VOLTAGE INSTABILITIES IN Al/Ta2O5-SiO2/Si STRUCTURES AND THEIR CONNECTION WITH J-V CHARACTERISTICS

Abstract: Flatband and current-voltage instabilities in unstressed Al/Ta 2 O 5 -SiO 2 /Si structures were studied in details. It has been found that, after an initial run left on fresh samples, both C-V and J-V characteristics exhibit repeatable patterns. Precisely repeatable counterclockwise hysteresis-like loop in C-V characteristics occurs, while no significant hysteretic behaviour is observed in static J-V characteristics. The reduced instability in J-V characteristics is explained by mutual compensation of two oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(53 reference statements)
1
1
0
Order By: Relevance
“…After this initial irreversible change, repeatable patterns of the − curves are obtained depending generally on the starting voltage. This is a common behavior of the metal/high-/SiO 2 /Si structures, as we have shown in [24].…”
Section: − Hysteresissupporting
confidence: 69%
See 1 more Smart Citation
“…After this initial irreversible change, repeatable patterns of the − curves are obtained depending generally on the starting voltage. This is a common behavior of the metal/high-/SiO 2 /Si structures, as we have shown in [24].…”
Section: − Hysteresissupporting
confidence: 69%
“…Namely, as we have shown in the work [22], voltage stress causes an increase of the capacitance in accumulation ( 0 ) by effective thinning of the SiO 2 layer by creation of conductive paths in this layer during the stress, as it was previously found from stress induced leakage current characteristics in the work [23]. Detailed study of the variations of − characteristics with consecutive runs has been reported in [24].…”
Section: − Hysteresismentioning
confidence: 68%